Research & Teaching Assistant: Jalan Lain Kuliah Gratis ke USA Selain dengan Beasiswa - Moh. Thoyib Syafi'i; Yuliana Friska; Anita Anggraini; Ani Kusumaningsih; Angga Hidayat (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
With the drastic increase in competition in the future, the readiness of human resources is an essential factor that should not be ignored. One way to prepare qualified human resources is through education. However, for some students, the cost of education in Indonesia is still too expensive, so not a few students are unable to continue their education to higher education. A team of lecturers from Pamulang University, in collaboration with Myskat Empat Ribu (MER) organized a fundraising webinar. This webinar aims not only to raise funds to be distributed to orphaned students who are threatened with dropping out of university but also to provide information to scholarship hunters. This webinar results in scholarship hunters knowing other programs to study abroad besides scholarships. Apparently, not many students/ lecturers do not know the research/teaching assistanceship program.